Going viral: How social and personal motivations drive emotional engagement and consumer online brand-related activities - Thi Cam Tu Dinh; Yoonjae Lee (PLoS ONE, 2025)
In today’s digital marketing landscape, viral brand campaigns succeed when consumers actively engage with and share brand messages across their social networks. Building on social exchange theory, this study examined what motivates people to emotionally connect with these campaigns and participate in consumer online brand-related activities (COBRAs). An online survey of 452 participants was conducted to examine the relationship between seven motivations, emotional engagement as a moderator, and COBRAs. The findings revealed that social motivations including the desire to interact, follow trends, build community, and stay connected strengthen emotional engagement with branded content and encourage sharing behavior. Personal motivations also proved significant, as individuals’ needs for self-presentation, self-expression, and self-assurance shaped both their emotional engagement and participation in brand-related activities. This research advances theoretical understanding in viral marketing, particularly regarding emotional engagement and COBRAs, while offering valuable insights for marketers seeking to design campaigns that resonate emotionally and socially with audiences.